Metal Nanoparticles and Clusters Advances in Synthesis, Properties and Applications (Springer International Publishing, 2018)
This book covers the continually expanding field of metal nanoparticles and clusters, in particular their size-dependent properties and quantum phenomena. The approaches to the organization of atoms that form clusters and nanoparticles have been advancing rapidly in recent times. These advancements are described through a combination of experimental and computational approaches and are covered in detail by the authors. Recent highlights of the various emerging properties and applications ranging from plasmonics to catalysis are showcased.